If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8(2q + -2) = 0 Reorder the terms: 8(-2 + 2q) = 0 (-2 * 8 + 2q * 8) = 0 (-16 + 16q) = 0 Solving -16 + 16q = 0 Solving for variable 'q'. Move all terms containing q to the left, all other terms to the right. Add '16' to each side of the equation. -16 + 16 + 16q = 0 + 16 Combine like terms: -16 + 16 = 0 0 + 16q = 0 + 16 16q = 0 + 16 Combine like terms: 0 + 16 = 16 16q = 16 Divide each side by '16'. q = 1 Simplifying q = 1
| 2(w^2-36)=0 | | 8x+4z=5+7y | | f(x)=3x^2+6x-4 | | 3e^2x=44 | | ln(x^5/x^4) | | 3x^2-5x+x^2-5x=x | | m=2/3.(7.-9) | | 3x^4-2x^3+22x^2-18x-45=0 | | -8=4+0.125b | | 2b^2+17b+35=0 | | 5(8y-9)-(7y+6)= | | 5y/y^2-2y | | 2cos(6x)+1=0 | | 4p-24=-4+8p | | 5y/y*2-2y | | 3m-20=-34+m | | 317g=kg | | 103x-4=-215x+632 | | x*x+10x=39 | | 3t*6p*5t= | | 2x+3y+2-y-8x-7= | | m+3m+5m-9= | | 5(5-d)-37=25d-6(2+5d) | | log(4)3x^2-1=x-1 | | 0=0.1t^2-3.5t+6 | | log(4)3x-1=x-1 | | -9+15x+6x=180 | | 16x*x+16x+4=0 | | log(4)3x=x-1 | | 16x=2x+7 | | Cos^42x-cos^24x=0 | | (2x+10)+(4x-10)=180 |